First report of leaf spot on kiwifruit caused by Phoma sp. in Korea. Issue 3 (2nd July 2016) - Kwon, Y; Hong, SW; Kwack, Y-B; Kwak, Y-S
ABSTRACT: Small, dark brown leaf spots consistent with symptoms caused by Phoma sp. were observed on kiwifruit ( Actinidia deliciosa cv. Hayward) at an orchard in Sacheon, South Korea. The causal agent was isolated from the spots and identified by morphological and molecular characteristics by sequencing the internal transcribed spacer region. To establish Koch's postulates, the pathogen was inoculated on to leaves in a pathogenicity test and reisolated from the developed lesions. Phoma sp. has been reported as a causal agent of kiwifruit leaf spot disease in New Zealand and Italy. However, this is the first report of leaf spot disease caused by Phoma sp. in Korea.